Facile Synthesis and X-ray Peak Broadening Studies of Zn1-xMgxO Nanopaiticles - Zak, A.K.; Yousefi, R.; Abd Majid, Wan Haliza; Muhamad, M.R. (2012)
Magnesium-doped ZnO nanoparticles (NPs) (Zn1-xMgxO-NPs, x = 0.0, 0.01, 0.03, and 0.05) were synthesized by a simple sol-gel method. The compounds were synthesized at calcination temperatures of 650 degrees C for 2 h. The synthesized Zn1-xMgxO-NPs were characterized by X-ray diffraction analysis (XRD) and high-magnification transmission electron microscopy (TEM). The XRD results revealed that the sample product was crystalline with a hexagonal wurtzite phase. The TEM showed Zn1-xMgxO-NPs with nearly spherical and hexagonal shapes. The size-strain plot (SSP) method was used to study the individual contributions of crystallite sizes and lattice strain on the peak broadening of the Zn1-xMgxO-NPs. Physical parameters such as strain, stress, and energy-density values were calculated more precisely for all reflection peaks of XRD corresponding to the wurtzite hexagonal phase of ZnO in the 20 degrees-100 degrees range from the SSP results. The effect of doping on the optical band-gap was also investigated. The results showed that Mg2+ is a good dopant to control some of the ZnO properties, with minimum defects to its structure. (C) 2011 Elsevier Ltd and Techna Group Sri. All rights reserved.